The Impact of Indirect Transport to a Trauma Centre on Survival for Major Trauma Patients: A National Propensity-Adjusted Observational Study - Davie, Gabrielle; Dicker, Bridget; Lilley, Rebbecca; Campbell, Nicola; Ameratunga, Shanthi; Civil, Ian; Branas, Charles; Reid, Papaarangi; de Graaf, Brandon; Montoya, Luisa; Kool, Bridget (International Journal of Population Data Science, 2026)
Introduction An optimally structured prehospital trauma care system can reduce the consequences of serious injuries. While trauma systems in some countries have adopted the policy of transporting major trauma patients directly to a trauma centre (TC) bypassing closer lower-level hospitals, other countries have been less directive in adopting this policy. Objective To explore the short-term survival of direct versus indirect transfer to a definitive care TC for major trauma patients injured in locations in Aotearoa New Zealand (NZ) where there was an opportunity for indirect transportation. Methods National administrative data from the NZ Trauma Registry and Emergency Medical Services (EMS) were linked. Major trauma patients for whom there was no hospital closer than the definitive care TC were excluded. Propensity-weighted adjusted models were used to compare mortality (2-week and 30-day) between those for whom EMS transported directly versus indirectly. Results Of 1,008 patients considered to have an opportunity for transfer, 370 (36.7%) were admitted at one hospital before their definitive care TC. Similar percentages of directly and indirectly transported patients died within 30 days (8.9% and 10.0% respectively; p = 0.6). Lower 2-week (aRR 0.64, 95%CI 0.38, 1.06) and 30-day mortality (aRR 0.70, 95%CI 0.42, 1.16) were observed for those transported indirectly. Older (≥55 years) indirectly transported patients were estimated to have a 30-day mortality aRR of 0.56 (95%CI 0.30, 1.05) that of those directly transported whereas, for younger patients, the direction and strength of evidence differed (aRR 1.31; 95%CI 0.64, 2.69). Conclusion For major trauma patients in NZ, this study found no evidence of a statistically significant difference in short-term mortality between those transported directly and indirectly, although point estimates suggest possible lower mortality, particularly for older patients, amongst those transported indirectly. Study limitations, including wide confidence intervals, are emphasised and additional research is needed to further confirm these findings and aid in nation-specific delivery of trauma care.